Fertilidade do solo e atividade micorrízica em áreas de agricultores familiares no norte de Minas Gerais - Sueli Gomes Fernandes (2011)
Farms properties in the community of Agua Boa 2, Rio Pardo de Minas(Minas Gerais) were characterized, according to the chemical, physical and activity of the arbuscular mycorrhizal fungi (AMF). For fertility evaluation, spores density, root colonization and levels of glomalin, soil samples were collected in a depth of 0-20 cm, in fourteen subsystems characterized as low input or agroecological transition, in 2010, in April. The mycorrhizal inoculum potential was determined by bioassay in a greenhouse, arranged in a completely randomized design, with three replications. The identification of AMF species was realized by soil samples of bioassay and trap cultures. The subsystems exhibit a good diversity of AMF species that were affected by fertility conditions areas and deployed by the host plants, which affected spore density and potential for root infection. The levels of glomalin were low and it was related to textural soil characteristics. From this study, it was possible to identify the necessity of accessible and proper practices incorporation to manage these soil properties such as green fertilization, cover plants and croprotation